2018
DOI: 10.1371/journal.pone.0201401
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen conserving mitochondrial adaptations in the skeletal muscles of breath hold divers

Abstract: BackgroundThe performance of elite breath hold divers (BHD) includes static breath hold for more than 11 minutes, swimming as far as 300 m, or going below 250 m in depth, all on a single breath of air. Diving mammals are adapted to sustain oxidative metabolism in hypoxic conditions through several metabolic adaptations, including improved capacity for oxygen transport and mitochondrial oxidative phosphorylation in skeletal muscle. It was hypothesized that similar adaptations characterized human BHD. Hence, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 32 publications
(45 reference statements)
5
30
0
Order By: Relevance
“…The lack of mitochondrial content fibre-type difference in the ND is supported by Hoppeller (1986) findings who likewise reported a similar mitochondrial content across the muscle fibres of trained individuals (Saltin et al 1977). Additionally, our findings are in agreement with Kjeld et al (2018) who showed a similar citrate synthase maximal enzyme activity in EBHD with ND controls. Qualitative assessment of the relative myoglobin and mitochondrial protein distribution in muscle fibres revealed, a stronger fluorescence intensity and a homogenous distribution of myoglobin and mitochondria at the sub-sarcolemmal regions of type I muscle fibres in the EBHD compared with ND.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…The lack of mitochondrial content fibre-type difference in the ND is supported by Hoppeller (1986) findings who likewise reported a similar mitochondrial content across the muscle fibres of trained individuals (Saltin et al 1977). Additionally, our findings are in agreement with Kjeld et al (2018) who showed a similar citrate synthase maximal enzyme activity in EBHD with ND controls. Qualitative assessment of the relative myoglobin and mitochondrial protein distribution in muscle fibres revealed, a stronger fluorescence intensity and a homogenous distribution of myoglobin and mitochondria at the sub-sarcolemmal regions of type I muscle fibres in the EBHD compared with ND.…”
Section: Discussionsupporting
confidence: 94%
“…No between group differences in fibre type distribution (type I vs type II) were observed in the present study. This is consistent with earlier observations made in EBHD and swimmers (Gollnick et al 1972; Kjeld et al 2018). However, contrary to Bae et al (2003), we failed to report any between group FA differences.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations